2012
DOI: 10.1089/jpm.2012.0152
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Patients, Caregivers, and Health Care Providers toward Background Music in Patient Care Areas: An Exploratory Study

Abstract: Background music in patient care areas was preferred to ordinary sound by patients, caregivers and providers. Demographics of the population are strong determinants of music style preferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
1
10
1
Order By: Relevance
“…The clinic itself may be customized for patients who have complex care needs, with low examining tables, a waiting room (or lack thereof) with an emphasize on privacy, ambient music, and standardized comprehensive palliative care assessments. 92,99,102 Moreover, the clinic can serve as a specialized setting for education and research. 100 This model also solidifies the independent role played by palliative care teams in cancer care rather than being seen as an appendage of individual oncology clinics.…”
Section: Outpatient Clinicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinic itself may be customized for patients who have complex care needs, with low examining tables, a waiting room (or lack thereof) with an emphasize on privacy, ambient music, and standardized comprehensive palliative care assessments. 92,99,102 Moreover, the clinic can serve as a specialized setting for education and research. 100 This model also solidifies the independent role played by palliative care teams in cancer care rather than being seen as an appendage of individual oncology clinics.…”
Section: Outpatient Clinicsmentioning
confidence: 99%
“…Clear referral criteria are set, prioritizing urgent same‐day referrals for patients with physical or psychosocial distress. The clinic itself may be customized for patients who have complex care needs, with low examining tables, a waiting room (or lack thereof) with an emphasize on privacy, ambient music, and standardized comprehensive palliative care assessments . Moreover, the clinic can serve as a specialized setting for education and research .…”
Section: Innovative Models Of Care Deliverymentioning
confidence: 99%
“…There were a few studies that examined attitudes towards music in the wider hospital setting. Overall patients responded positively and welcomed background music, recognising that it could improve mood and relieve pain (Kilic et al., ; Perez‐Cruz et al., ). For those studies that examined the individual effects of music listening, the selection of music style was often made by the study investigators.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, early postoperative rehabilitation exercises can aid the improvement of the blood and lymph circulation and reduce limb swelling and pain perception. 30,31 Previously, Kronborg et al 32 reported that it was feasible to initiate progressive knee straighter strength training for fractured limbs in acute wards, which could reduce force asymmetry between limbs without increasing hip pain. In the present study, the muscle training device was used to achieve muscle relaxation mainly through repeated contractions and relaxation.…”
Section: Discussionmentioning
confidence: 99%